Does color really matter? Reliability of transcutaneous bilirubinometry in different skin-colored babies - Pearl Mary Varughese; Lalitha Krishnan; Ravichandran (Indian Journal of Paediatric Dermatology, 2018)
Background: Transcutaneous bilirubinometry, in keeping with rapid technological advances, has come a long way as an effective tool for assessing bilirubin levels in newborns. Though the early devices showed changes due to melanin concentration, the new generation devices were based on micro-spectrometry. Color coded scales were rarely used for the comparison. Hence the primary outcome is that TcBI is more reliable in lighter skin color babies than darker skin color babies.Objective: To study the reliability of TcB in different skin color babies. Materials and Methods: The study was conducted in a tertiary newborn center from November 2014 to June 2016. The inclusion criteria included all babies above 34 weeks gestation and exclusion criteria included babies with established direct hyperbilirubinemia, neonatal septicemia, major congenital/ gastrointestinal malformations and those on phototherapy. 396 babies were recruited. At 24 hours, babies were categorized based on Fitzpatrick skin color chart. Statistical analysis was done using the ROC curves Bland Altman charts. Results: Mean TcB was found to be uniformly higher than TSB for all variables like sex, birth weight, gestational age and growth of the baby with an excellent correlation (r = 0.698-0.932). 335 babies (74.4%) were falling in the color code 3. 113 babies (25.1%) were in the color code 4 and 2 babies (0.4%) were in the color code 5. TcB correlates better in light skin tone babies (color code 3) than dark skin tone babies (color code 4) with r= 0.874 and r= 0.856 respectively. Conclusion: Though TcB overestimates; it correlates well with TSB in lighter skin tone babies than babies with darker skin tone.